Pyrene Carboxylate Ligand Based Coordination Polymers for Microwave-Assisted Solvent-Free Cyanosilylation of Aldehydes - Karmakar, Anirban (Molecules, 2021)
The new coordination polymers (CPs) [Zn(μ-1κO(1):1κO(2)-L)(H(2)O)(2)](n)·n(H(2)O) (1) and [Cd(μ(4)-1κO(1)O(2):2κN:3,4κO(3)-L)(H(2)O)](n)·n(H(2)O) (2) are reported, being prepared by the solvothermal reactions of 5-{(pyren-4-ylmethyl)amino}isophthalic acid (H(2)L) with Zn(NO(3))(2).6H(2)O or Cd(NO(3))(2).4H(2)O, respectively. They were synthesized in a basic ethanolic medium or a DMF:H(2)O mixture, respectively. These compounds were characterized by single-crystal X-ray diffraction, FTIR spectroscopy, thermogravimetric and elemental analysis. The single-crystal X-ray diffraction analysis revealed that compound 1 is a one dimensional linear coordination polymer, whereas 2 presents a two dimensional network. In both compounds, the coordinating ligand (L(2−)) is twisted due to the rotation of the pyrene ring around the CH(2)-NH bond. In compound 1, the Zn(II) metal ion has a tetrahedral geometry, whereas, in 2, the dinuclear [Cd(2)(COO)(2)] moiety acts as a secondary building unit and the Cd(II) ion possesses a distorted octahedral geometry. Recently, several CPs have been explored for the cyanosilylation reaction under conventional conditions, but microwave-assisted cyanosilylation of aldehydes catalyzed by CPs has not yet been well studied. Thus, we have tested the solvent-free microwave-assisted cyanosilylation reactions of different aldehydes, with trimethylsilyl cyanide, using our synthesized compounds, which behave as highly active heterogeneous catalysts. The coordination polymer 1 is more effective than 2, conceivably due to the higher Lewis acidity of the Zn(II) than the Cd(II) center and to a higher accessibility of the metal centers in the former framework. We have also checked the heterogeneity and recyclability of these coordination polymers, showing that they remain active at least after four recyclings.